Cardiac tumours: clinical, echocardiographic and pathological features - Silva,Ricardo Pereira (2003)
OBJECTIVE: The purpose of our paper was clinical and echocardiographic characterisation of patients with cardiac tumours and the evaluation of the surgery and tumour recurrence. METHOD: The first part of research was a retrospective investigation to identify cardiac tumours identification and to collect data from patients' records of the Messejana Hospital and Walter Cantídio University Hospital, from 1981 to 2001. In this period, 19 cases of cardiac tumours were discovered. The patients were submitted to clinical, electrocardiographic and echocardiographic re-evaluation from March to July 2002. RESULTS: Congestive symptoms and thoracic pain were the most frequent symptoms. The location in which most of the tumours were identified was left atrium. Among patients submitted to surgery, all of them had the tumour extracted from atrium. The most common histopathologic type was myxoma (78%). Surgical mortality was 14%. Tumour recurrence occurred in one patient. CONCLUSION: Cardiac tumours were more frequent in left atrium, benign tumours were more frequent than malignant tumours, and the most frequent histopathologic type was myxoma.